PENERAPAN STRATEGI BELAJAR PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SEKOLAH DASAR - Mukmin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The problem in this research is the result of a IPS class V SDN 58 Balai Makam, still low with an average value of 67.61. The purpose of this research is to improve student learning outcomes in IPS the application of learning strategies concept maps in the class V SDN 58 Balai Makam. This study is a class act with 2 cycles. It can be seen in student learning outcomes the average value of 67.61 increased to 70.28 in cycle I. From the first cycle to the second cycle increased by 77.52. Overall increased 14.66%. The average percentage of classical completeness of student learning outcomes also increased. At the score of the first cycle of 66.66%, and the second cycle increased to 85.71%. So overall completeness of the classic rose 28.56%. In the teachers' activities has increased in each cycle. While in the first cycle the average percentage of the activity of the teacher with 66.66% in both categories increased to 81.25% with the category very well in the second cycle. So overall there is an increase in activity of the teacher of 21.89%. At the student activity also increased in each cycle. In the first cycle of an average percentage of 64.58% with the good category increased to 77.08% in the second cycle. So overall there is an increase in the activity of students 19.36%. Application of Learning strategies concept maps can improve learning outcomes of students in class V SDN 58 Balai Makam.